Copyright, interrupted : building trust in blockchain-based content platforms - Tan, Corinne (2022)
Are blockchains the solution to the disruption of copyright on digital content platforms? While the fundamental features of blockchains, being permanence, transparency and their quality of being decentralized records, may appear suited to fill the gaps left by copyright laws and alleviate some problems for content owners, there are challenges to their use. I argue in this article that trust is a necessary element for blockchain-based content platforms to fulfil their revolutionary potential in the copyright realm.